Experimental and analytical study of cracks under biaxial fatigue - Mokhtarishirazabad, Mehdi; López-Crespo, Pablo; Moreno-Morales, María Belén; Camas-Peña, Daniel; López-Moreno, A.; Zanganeh, M (GIF, 2016)
Most mechanical components experience multi-axial cyclic loading conditions during service. Experimental analysis of fatigue cracks under such conditions is not easy and most works tend to focus more on the simpler but less realistic case of uni-axial loading. Consequently, there are many uncertainties related to the load sequence effect that are now well known and are not normally incorporated into the growth models. The current work presents a new methodology for evaluating overload effect in biaxial fatigue cracks. The methodology includes evaluation of mixed-mode (KI and KII) stress intensity factor and the Crack Opening Displacement for samples with and without overload cycle under biaxial loading. The methodology is tested under a range of crack lengths. All crack-tip information is obtained with a hybrid methodology that combines experimental full-field digital image correlation data and Williams' elastic model describing the crack-tip field.
Keywords: Materiales -- Fatiga; Stress intensity factor; Biaxial fatigue; Mixed-mode; Crack opening displacement